2021
DOI: 10.4103/bc.bc_21_21
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 for Parkinson's disease

Abstract: This review article discusses the preclinical evidence and clinical trials testing the use of a peptide agonist of the glucagon-like peptide (GLP) receptor that promotes insulin secretion in the animal models of and patient with Parkinson's disease (PD). In particular, we focus on the therapeutic effects of the GLP receptor agonist exendin-4, also called exenatide, in PD. The ultimate goal of this article is to provide a critical assessment of the laboratory and clinical data toward guiding the translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…As N-palmitoyl serinol acts as an agonist for GPR119, we aimed to confirm whether it has a similar neuroprotective effect to the GLP-1 family of proteins that has recently attracted attention [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As N-palmitoyl serinol acts as an agonist for GPR119, we aimed to confirm whether it has a similar neuroprotective effect to the GLP-1 family of proteins that has recently attracted attention [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Phase II clinical trial, exenatide, an agonist of the GLP-1 receptor, showed great protective effects in PD patients. 572 NLY01, a different GLP-1 receptor agonist that can protect dopaminergic neurons from inflammatory responses elicited by glial cells, 573 has been enrolled recently in a Phase II clinical trial. The GLP-1 analogue semaglutide showed multiple benefits in a MPTP-induced PD mouse model: it reduced the accumulation of α-synuclein, alleviated chronic inflammation, attenuated the peroxidation of lipid, inhibited the mitophagy related signaling and increased the expression of glial cell line-derived neurotrophic factor (GDNF).…”
Section: Immune-directed Therapiesmentioning
confidence: 99%
“…Embora várias investigações pré-clínicas tenham relatado potencial neuroprotetor dos inibidores de DPP4 em vários distúrbios neurodegenerativos. A ativação de GLP1 mediada por DPP4 tem relação direta com a neurotransmissão monoaminérgica e a síntese de dopamina e, portanto, pode ter um papel importante na patologia da DP (Esparza-Salazar et al, 2021). No entanto, relatórios de ensaios clínicos pré-clínicos e randomizados controlados sugerem que a ativação do receptor GLP1 reduz o risco da DP e melhora as funções motoras.…”
Section: Inibidores Da Dipeptidil Peptidase 4 (Dpp4)unclassified